2014
DOI: 10.2140/gt.2014.18.1437
|View full text |Cite
|
Sign up to set email alerts
|

A mirror theorem for the mirror quintic

Abstract: ABSTRACT. The celebrated Mirror Theorem states that the genus zero part of the A model (quantum cohomology, rational curves counting) of the Fermat quintic threefold is equivalent to the B model (complex deformation, variation of Hodge structure) of its mirror dual orbifold. In this article, we establish a mirror-dual statement. Namely, the B model of the Fermat quintic threefold is shown to be equivalent to the A model of its mirror, and hence establishes the mirror symmetry as a true duality. CONTENTS

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…We will now describe the Chen-Ruan cohomology of the mirror quintic W . For more detail, refer to [18]. For an element g ∈ G, denote by [g] the corresponding element inḠ and I(g) := {k ∈ {1, 2, 3, 4, 5} | Θ k (g) = 0}.…”
Section: Gromov-witten Theory Of the Mirror Quinticmentioning
confidence: 99%
See 2 more Smart Citations
“…We will now describe the Chen-Ruan cohomology of the mirror quintic W . For more detail, refer to [18]. For an element g ∈ G, denote by [g] the corresponding element inḠ and I(g) := {k ∈ {1, 2, 3, 4, 5} | Θ k (g) = 0}.…”
Section: Gromov-witten Theory Of the Mirror Quinticmentioning
confidence: 99%
“…Thus one must first check convergence in order to prove the LG/CY correspondence. For the purposes of this paper however, the necessary convergence will follow from the mirror theorem of [18] . This is no longer true for the mirror quintic.…”
Section: Quinticmentioning
confidence: 99%
See 1 more Smart Citation
“…A mirror Y to the quintic 3-fold arises [7,22,47] as a crepant resolution of an anticanonical hypersurface in X = P 4 /(Z/5Z) 3 . A mirror theorem for Y has been proved by Lee-Shoemaker [61]. The variety Y is a Calabi-Yau 3-fold with h 1,1 (Y ) = 101.…”
Section: Introductionmentioning
confidence: 97%
“…They further showed that the narrow sectors of the FJRW state space correspond to the ambient cohomology of H * CR ([X W /G]). The LG/CY correspondence has been verified in genus zero for the Fermat Quintic withG = {1} [CR10]; for the narrow/ambient part of a general hypersurface in Gorenstein weighted projective space withG = {1} [CIR14]; for the mirror quintic (with groupG = (Z/5) 3 ) [PS13,LS12]; and for arbitrary Fermat polynomials with arbitrary admissible groups [PLS14]. This last paper [PLS14] is also interesting because it connects the LG/CY correspondence to the better-understood Crepant Transformation Conjecture.…”
Section: Landau-ginzburg/calabi-yau Correspondencementioning
confidence: 99%